Wearable‐Supported Physical Education for Physical Activity and Psychosocial Beliefs in Underserved Adolescents - Suryeon Ryu; Emily Kringle; Zan Gao (Journal of School Health, 2026)
ABSTRACT Background Despite well‐established health benefits of moderate‐to‐vigorous physical activity (MVPA), many youth, especially from low‐income households, remain insufficiently active. This study examined the feasibility and preliminary efficacy of a fitness wearable‐supported intervention to increase MVPA in physical education (PE) classes among underserved adolescents. Methods Four PE classes ( N = 55 enrolled; ages 11–14) at a low‐income public school were assigned to either a two‐week wearable‐supported PE or usual PE, and analyses included the 52 students with pre‐ and post‐assessment data. Feasibility benchmarks (recruitment, retention, data completeness, adherence, dose, technology) were compared against benchmarks set a priori. Between‐group differences in change in MVPA (actigraphy) and psychosocial beliefs (questionnaires) were analyzed using ANCOVA or non‐parametric equivalent tests. Results Recruitment, retention, data collection, and technology adherence benchmarks were met. A significant interaction for MVPA of in‐class PE was observed ( F (1, 47) = 14.60, p < 0.01, = 0.24), favoring the intervention group. No significant improvements in psychosocial beliefs were observed in either group. Implications for School Health Policy, Practice, and Equity Schools and health professionals may consider integrating digital health tools, aligned with evidence‐based pedagogical strategies and behavior change techniques to facilitate health‐enhancing physical activity. Conclusions Self‐monitoring and real‐time feedback via fitness wearables may increase in‐class engagement in MVPA among underserved adolescents, however, further studies are warranted to strengthen the evidence in this population.